A delay-aware cyber-physical architecture for wide-area control of power systems. (March 2017) - Soudbakhsh, Damoon; Chakrabortty, Aranya; Annaswamy, Anuradha M.
Abstract: In this paper we address the problem of wide-area control of power systems using Synchrophasor measurements in the presence of network delays. We propose a novel cyber-physical architecture that uses an arbitrated network control systems approach for mitigating the destabilizing effects of delays in power systems. The approach consists of: (1) utilization of Synchrophasor measurements from distributed measurements across different buses in the power network, (2) estimation of delays that control messages experience, (3) a delay-aware control design that explicitly accommodates the delays and judiciously utilizes estimated system states when needed, and (4) a switching control strategy that aborts the computation of control signals when delays exceed a certain threshold to improve resource utilization. While the control gains are determined using a centralized power system model and state feedback, it is shown that the delay-aware aspects of the proposed architecture allow both distributed measurements and distributed implementation of the control law. The results are illustrated using a 50-bus, 14-generator, 4-area power system model. The results clearly demonstrate that the proposed controller recovers the ideal system performance (such as deviations in frequency < 3 mHz ) even in the presence of large intra-area and inter-area delays with a small amount of additional control effort. Using the proposed overrun strategy, the results also confirm that about 30% drops can be accommodated with the proposed arbitrated network control systems approach. Abstract : Highlights: A cyber-physical architecture with distributed measurements for wide-area control. Delay-aware design using arrival rates of messages and service rates of processors. Proof of stability of the overall delay-aware arbitrated control design. Switching controller between nominal and abort modes to accommodate varying delay. Simulations using a 50 bus, 14 generator, 4 area system with realistic delays.